Antenatally diagnosed subdural haemorrhage in congenital factor X deficiency. Issue 10 (October 1988) - de Sousa, C; Clark, T; Bradshaw, A
Abstract : The presence of a subdural haemorrhage was observed in a fetus during antenatal ultrasound examination. The infant was found to be a homozygote for factor X deficiency. Prompt recognition permitted replacement treatment from an early stage. Inherited coagulation disorders should be suspected when intracranial haemorrhage is detected antenatally.